The Lima Inquisition the plight of crypto-Jews in seventeenth-century Peru - Schaposchnik, Ana E.; Project Muse (Madison, Wisconsin The University of Wisconsin Press, 2015)
Intro -- Contents -- Acknowledgments -- Introduction -- 1. Heresy and Inquisition in the Iberian World -- 2. The Trial as a Setting for Confession and Repentance -- 3. A Cobbler and a Merchant -- 4. A Community under Trial in Colonial Peru -- 5. The Inner World of the Lima Prisons -- 6. The Plight of the Condemned -- Conclusion -- Notes -- Bibliography -- Index.
Includes bibliographical references and index
Online-Ausg.
Keywords: Catholic Church -- Peru -- History -- 17th century; Crypto-Jews -- Peru -- History -- 17th century; Inquisition -- Peru -- Lima -- History -- 17th century; Crypto-Jews - Peru - History - 17th century; Electronic books; Peru -- History -- 1548-1820